Forensic profiling of non-volatile organic compounds in soil using ultra-performance liquid chromatography: a pilot study - Loong Chuen Lee; Ab Aziz Ishak; Ameeta A/P Nai Eyan; Anas Fahmi Zakaria; Nurul Syahiera Kharudin; Nor Azman Mohd Noor (Oxford University Press, 2021)
Soil is of particular interest to the forensic community because it can be used as valuable associative evidence to link a suspect to a victim or a crime scene. Liquid chromatography is a powerful analytical tool for organic compound analysis. Recently, high-performance liquid chromatography (HPLC) has proven to be an efficient method for forensic soil analysis, especially in discriminating soils from proximity locations. However, ultra-performance liquid chromatography (UPLC), which is much more sensitive than HPLC, has never been explored in this context. This study proposed a UPLC method for profiling non-volatile organic compounds in three Malaysian soils (red, brown and yellowish-brown soils). The three soils were analysed separately to assess the effects of individual chromatographic parameters: (a) elution programme (isocratic vs. two gradient programmes); (b) flow rate (0.1 vs. 0.2 mL/min); (c) extraction solvent (acetonitrile vs. methanol) and (d) detection wavelength (230 vs. 254 nm). The injection volume and total run time were set to 5 µL and 35 min, respectively. Consequently, each soil sample gave 24 different chromatograms. Results showed that the most desirable chromatographic parameters were (a) isocratic elution; (b) flow rate at 0.2 mL/min and (c) acetonitrile extraction solvent. The proposed UPLC system is expected to be a feasible method for profiling non-volatile organic compounds in soil, and is more chemical-efficient than a comparable HPLC system. Supplemental data for this article are available online at. Key points UPLC is a chemical-efficient analytical method for profiling non-volatile organic compounds in soil. Mobile phase rich in acetonitrile promotes separation of non-volatile organic compounds in soil. Isocratic elution is more desirable than gradient elution in producing a high-quality chromatogram.